Culture medium development for microbial-derived surfactants production: an overview - Abdul Hamid, Nurfarahin; Mohamed, Mohd Shamzi; Phang, Lai Yee (M D P I AG, 2018)
Surfactants are compounds that can reduce the surface tension between two different phases or the interfacial tension of the liquid between water and oil, possessing both hydrophilic and hydrophobic moieties. Biosurfactants have traits that have proven to be advantageous over synthetic surfactants, but these compounds do not compete economically with synthetic surfactants. Different alternatives increase the yield of biosurfactants; development of an economical production process and the usage of cheaper substrates during process have been employed. One of the solutions relies on the suitable formulation of a production medium by including alternative raw materials sourced from agro-wastes, hydrocarbons, or by-products of a process might help in boosting the biosurfactant production. Since the nutritional factors required will be different among microorganisms, the establishment of a suitable formulation for biosurfactant production will be challenging. The present review describes various nutrients and elements considered in the formulation of a production medium with an approach focusing on the macronutrient (carbon, nitrogen source, and C/N ratio), minerals, vitamins, metabolic regulators, and salinity levels which may aid in the study of biosurfactant production in the future.